Effect of prolonged administration of pegylated interferon/ribavirin therapy in genotypes 2a and 2b: Propensity score‐matched analysis. Issue 2 (February 2015) - Yokoyama, Satoe; Kawakami, Yoshiiku; Imamura, Michio; Hayes, C Nelson; Kohno, Hiroshi; Kohno, Hirotaka; Tsuji, Keiji; Aisaka, Yasuyuki; Kira, Shinsuke; Yamashina, Keitarou; Nonaka, Michihiro; Takahashi, Shoichi; et al.
Abstract Background and Aim Chronic hepatitis C genotype 2 patients show high susceptibility to pegylated interferon plus ribavirin therapy (PEG/RBV). However, the differences in response to therapy between genotypes 2a and 2b, and the efficacy of prolonged therapy for refractory patients have not been evaluated. We investigated the differences in response to PEG/RBV between each genotype and examined the efficacy of prolonged therapy. Methods A total of 343 chronic hepatitis patients infected with hepatitis C virus (HCV) genotype 2 (2a: n = 195; 2b: n = 148) were enrolled in this study. All patients received PEG/RBV for 24 (24 week group, n = 242) or more weeks (prolonged group, n = 101). We analyzed the differences in virological response between genotypes 2a and 2b. Clinical and virological factors of patients in the 24‐week group and the prolonged treatment group were matched using propensity score analysis, and the efficacy of prolonged therapy established by comparing time of serum HCV disappearance for each genotype. Results Virological response tended to be higher for genotype 2a compared with genotype 2b; however, there was no significant difference in sustained virological response rates between genotypes (2a: 78.3%; 2b: 70.2%; P = 0.19). After propensity score matching, the adjusted P‐value for sustained virological response rate was significantly different for genotype 2b patients with undetectable HCV‐RNA between weeks 5 and 8, and for genotype 2a patients with detectable HCV‐RNA at week 8. Conclusion Prolonged therapy with PEG/RBV may be effective when serum HCV‐RNA is detectable at week 4 and week 8 for genotype 2b and 2a patients, respectively.